2007
DOI: 10.1163/156853907780713046
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variation in the long-distance vocalizations of spotted hyenas

Abstract: SummaryIt has long been recognized that vocal signals communicate information about the age, sex and affective state of callers. However, the mechanisms by which these types of information are communicated are less well understood. Here we investigated variation in the acoustic properties of the long-distance vocalizations, called 'whoops', emitted by free-living spotted hyenas, Crocuta crocuta. Specifically we investigated whether the fundamental frequency, length and rate of whoops provide information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Our recent findings also support this, as in the case of playbacks of various dog vocalizations, the sounds containing shorter calls (along with shorter inter-call intervals) were rated to be more positive [22]. It was found in several other species that besides call length, inter-call intervals can be important indicators of arousal level, because the pauses between utterances shorten with a rise in arousal (mongoose: [38], hyena: [39], baboon: [40] pig: [14]). Nevertheless, studies showing the link between these temporal acoustic variables and emotional valence are scarce thus far.…”
Section: Discussionsupporting
confidence: 73%
“…Our recent findings also support this, as in the case of playbacks of various dog vocalizations, the sounds containing shorter calls (along with shorter inter-call intervals) were rated to be more positive [22]. It was found in several other species that besides call length, inter-call intervals can be important indicators of arousal level, because the pauses between utterances shorten with a rise in arousal (mongoose: [38], hyena: [39], baboon: [40] pig: [14]). Nevertheless, studies showing the link between these temporal acoustic variables and emotional valence are scarce thus far.…”
Section: Discussionsupporting
confidence: 73%
“…Status signalling is almost certainly not restricted to giggles. The whoop is used to transfer information to remote congeners and may allow individual identification of the sender as well as its current emotional state over distances up to 5 km [51,53,73,74]. Not only are whoop calls highly idiosyncratic making but it is also known that mothers will respond to the whoop from their own cub more frequently than to the whoop of a non-kin cub, demonstrating that the individual characteristics in the whoop sounds are recognized and utilized [73].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, "whoops," with long inter-whoop intervals, are primarily used to signal separated individuals, supporting within- and between-clans acoustic interaction [51,52]; conversely, the "grunt" [39] ("soft growl" in [49]) is uttered during close meeting of clan mates and remains barely audible after a few meters of propagation. Previous studies have focused on the long-distance "whoop" call, showing that it supports information related to sex and individual identity and thus may allow discrimination between clan members and alien individuals [48,51,53]. Although they might play an important role in mediating the relationships within the clan, calls, other than the whoop, of adult hyenas have been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Spotted hyenas can vary the duration of these inter-whoop intervals, resulting in faster or slower calls. Theis et al [115] found that the interwhoop interval encodes information about the current emotional state of the caller and that hyenas respond to this information. Whoop bouts emitted by juveniles during periods of social excitement have shorter inter-whoop intervals, and conspecifics are significantly more likely to respond to these whoop bouts by approaching the caller.…”
Section: Relative Numerosity Judgements In the Wildmentioning
confidence: 99%